A Bumpy Ride for China’s Belt and Road Initiative in Kazakhstan: Findings from a University Survey - Christopher B. Primiano; Alma Kudebayeva (Journal of Current Chinese Affairs)
China's Belt and Road Initiative (BRI) has been a polarising issue throughout the world, with analysts viewing it as either advancing China's desire to remake the world according to its plans, having the potential for, or indeed about, mutual benefit, or too ad-hoc and thus impossible to predict how it will develop. In this article, we present our findings from a survey that we conducted with university students in Almaty, Kazakhstan on views towards BRI. There are two main findings. First, the majority of our participants view BRI as bad for Kazakhstan. Second, one's political views, specifically whether one embraces authoritarian or conservative views (on the one hand) or democratic views (on the other), correlate with the way that person views BRI. In particular, we found that those who espouse authoritarian or conservative views consistently and with statistical significance view the initiative in higher regard than those who embrace democratic political views. To explain this pattern, we draw from social identity theory.